Can protected areas mitigate the impacts of climate change on bird's species and communities?. Issue 6 (9th February 2016) - Gaüzère, Pierre; Jiguet, Frédéric; Devictor, Vincent
Abstract: Aim: Protected areas (PAs) are the mainstay of our conservation strategies. While they may succeed in locally preventing species and habitat degradation due to human activities, their ability to mitigate the impacts of climate change on biodiversity is still debated. We assessed whether community and species responses to climate change were related to PAs by testing three main predictions: (1) the thermal adjustment of community composition to temperature changes should be positively related to the proportion of PAs, (2) the species that benefit most from PAs should be less impacted by temperature change, and (3) the species a priori considered the most vulnerable to global change should be even more sensitive to the mitigating effect of PAs. Location: Mainland France. Methods: Data from a long‐term, large‐scale standardized monitoring programme, recording annual changes in the abundance of 116 breeding bird species in France between 2001 and 2012, were used. Local temporal trends in spring temperature, community reshuffling and bird populations over the country were estimated with a moving window approach (2094 spatial windows). Generalized additive mixed models were then performed to relate these responses to the local proportion of PAs. Results: Most PAs promote community adjustment to temperature changes. At the species scale, our results show that the more a species benefited from PAs, the less vulnerable it was to temperature changes. PAs were also more effective in mitigating the impact of climate change on the less common and northernmost birds. Main conclusion: Protected areas do seem to mitigate climate change impacts on species and communities. Our study argues for the use of integrative frameworks at different biological scales to assess the usefulness and relevance of PAs faced with climate change and suggests that PAs remain key effective conservation strategies in a changing climatic world.